Coping with Drug Abuser in the Family: A Qualitative Study in Penang, Malaysia - Paramjit Singh Jamir Singh; Azlinda Azman; Syazwani Drani (Asian Social Work Journal, 2019)
Drug use in Malaysia has steadily increased over the past decade. Drug addiction does not only affect the addict, but it also impacts the lives of their family members. This qualitative study seeks to explore how the drug user’s family members cope with the drug abuse problems in the family. A total of 20 respondents, acting as heads of their families, from the state of Penang, were interviewed. The findings indicated that the respondents utilized both problem-focused and emotion-focused coping strategies to cope with the drug addiction problems in the family. The respondents in this study also used both formal and informal social support systems to cope with the drug abuse problems caused by drug abuse within the family. This study suggests that the drug user’s family members should engage themselves in self-help and support groups to find and learn about constructive coping strategies used by other families who have a similar experience in dealing with drug abuse problems in the family. In addition, by engaging themselves in self-help and support groups, it will help the drug user’s family members gain emotional and social support from other drug user’s family members.